The Effect of Monetary Policy on the Performance of the Manufacturing Industry Sector in Indonesia - Arif Prihatin; Siti Aisyah (Urecol Journal. Part B: Economics and Business, 2022)
The manufacturing sector has the ability to generate higher output, which performance can be affected by monetary policy. The main sector in Indonesia national development due to its considerable contribution to national income and strong linkages to other sectors, hence the importance to monitor policies that can significantly affect its productivity. This study aims to analyze the effect of the exchange rate, lending facility interest rate, foreign exchange reserves and the money supply on the output of the manufacturing industry sector in Indonesia 2016Q1-2021Q3. The data in this study are secondary time series data from 2016Q1-2021Q3. The analytical tool used in this research is OLS (Ordinary Least Square). Based on the results of the analysis, it is found that the variables that have a significant effect on the output of the manufacturing industry sector are the exchange rate, lending facility interest rate, and foreign exchange reserves. While money supply has no effect on the output of the manufacturing sector.